2018
DOI: 10.3897/zookeys.738.21021
|View full text |Cite
|
Sign up to set email alerts
|

First record of larvae of the water mite Hydrachna processifera Piersig, 1895 from Turkey (Acari, Hydrachnidia, Hydrachnidae)

Abstract: Larvae of water mite Hydrachna processifera Piersig, 1895 (Acari, Hydrachnidiae) were reported on diving beetles Dytiscus marginalis Linnaeus, 1758 (Coleoptera, Dytiscidae) from Turkey. The redescription of the larva was made. Earlier, the larva H. processifera was described as H. inermis, but it was subsequently synonymized with H. processifera. The larva of H. processifera is a new record for the Turkish fauna. All larvae of H. processifera were found on the mesosternum of the one specimens (prevalence = 16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The larva of Hydrachna sp. is most similar to larvae of H.processifera described by Wainstein (1980) as a H.inermis (Aykut et al 2018). It is similar in the shape of coxal plates, the discoidal hypostomal sucker, the tibiotarsus relatively long with two claws the same size, weakly bent; five tibiotarsal spines the same size.…”
Section: Taxonomic Accountsupporting
confidence: 80%
See 1 more Smart Citation
“…The larva of Hydrachna sp. is most similar to larvae of H.processifera described by Wainstein (1980) as a H.inermis (Aykut et al 2018). It is similar in the shape of coxal plates, the discoidal hypostomal sucker, the tibiotarsus relatively long with two claws the same size, weakly bent; five tibiotarsal spines the same size.…”
Section: Taxonomic Accountsupporting
confidence: 80%
“…The water mites of subcohort Hydrachnidiae are well known as parasites of water beetles. Larval instars of the genus Acherontacarus Angellier attach to the mesosternal region of their host beetles (Aykut et al 2018), larvae of the genus Hydrachna Muller attach to thorax and abdomen sternites and tergites under the elytra (Zawal 2002), while larvae of genus Eylais Latreille mostly hide under the beetle’s elytra (Zawal 2003b). In this study, we found three larvae of Hydrachna sp.…”
Section: Introductionmentioning
confidence: 99%
“…Corixids from Doñana are commonly parasitized by two water mite species: Hydrachna skorikowi (Family Hydrachnidae) and Eylais infundibulifera (Koenike, 1897; Family Eylaidae) (see S3 Table and [20]). Larvae of Hydrachnidae are strictly aquatic and can use dissolved oxygen from the water; besides Nepomorpha (Heteroptera), they also parasitize other aquatic insects such as Dytiscidae and Hydrophilidae (Coleoptera) [38]. Eylais larvae are aerial [39], requiring an air-oxygen supply to survive, and are restricted to areas such as under the wings, tergites, the underside of the elytra and hemelytra of the host [40, 41].…”
Section: Methodsmentioning
confidence: 99%